Migration Externalities in Chinese Cities - Pierre-Philippe Combes; Sylvie Démurger; Shi Li (Institute for the Study of Labor (IZA), 2015)
We analyse the impact of internal migration in China on natives' labour market outcomes. We find evidence of a large positive correlation of the city share of migrants with natives' wages. Using different sets of control variables and instruments suggests that the effect is causal. The large total migrant impact (+10% when one moves from the first to the third quartile of the migrant variable distribution) arises from gains due to complementarity with natives in the production function (+6.4%), and from gains due to agglomeration economies (+3.3%). Finally, we find some evidence of a stronger effect for skilled natives than for unskilled, as expected from theory. Overall, our findings support large nominal wage gains that can be expected from further migration and urbanisation in China.
Keywords: O18; J61; R23; J31; O53; 330; migration; urban development; agglomeration economies; wage disparities; China